Analysis of early childhood education teacher preparedness in implementing the Merdeka Curriculum - Wahyuningtyas, Dessy Putri; Mahya, Isyna Ainim; Fitria, Rofidah Nur; Lestari, Dewi (Psychology, Evaluation, and Technology in Educational Research, 2023)
Early childhood education (ECED) plays an important role in forming the basis of children's intellectual, emotional, and social development in the early stages of their lives. In Indonesia, one of the important initiatives in improving the quality of education is the Merdeka Curriculum. This curriculum aims to give teachers the freedom to develop innovative and relevant learning methods. Malang City, as one of the education centers in Indonesia, has also adopted the Merdeka Curriculum in an effort to improve the quality of early childhood education. However, the successful implementation of the Merdeka Curriculum largely depends on the extent to which ECD teachers understand, plan, and implement learning in accordance with the demands of the curriculum. Therefore, educational researchers and practitioners need to conduct an in-depth analysis related to the readiness of ECD teachers to face this curriculum change. This study used a survey research method through questionnaires given to 158 teachers from 70 RA schools in Malang city. The survey results were then analyzed using descriptive statistical methods. Based on the indicators in this study, researchers found that 88% of teachers already have readiness in lesson planning. 81% of teachers already have readiness in learning implementation, and 74.1% of teachers are capable or have readiness in evaluating learning in the Merdeka Curriculum. Teachers understand the Merdeka curriculum but in implementation or implementation and conducting assessments that are not in accordance with the nomenclature of the Merdeka Curriculum, especially for Early Childhood Education Institutions (PAUD). So, there needs to be a Joint Effort between various parties to increase teachers' understanding of the curriculum, obtain support for the integration of values in learning relevant training, and introduce holistic assessment methods.